The effect of the hydrothermal alteration associated with the Saffy East Fault on the UG2 reef at Saffy Shaft of Lonmin Platinum, Western Limb of the Bushveld Complex - Kondlo, Lusanda (My University, 2021)
The UG2 chromitite layer of the western limb of the Bushveld Complex has been mined extensively and studied for its economic importance. The UG2 is defined as a fine-grained dark grey to black in colour, chromitite layer of approximately 1.2 m in thickness, consisting mainly of chromite, orthopyroxene and plagioclase. The UG2 chromitite layer is well-known as the world’s largest platinum group elements (PGEs) bearing horizon. Most studies that have been conducted on this economic horizon focus on the normal UG2 chromitite layer and little research on the hydrothermal altered UG2 chromitite has been documented. The presence of hydrothermal altered UG2 at Saffy Shaft at Lonmin Platinum is prevalent within the eastern block of the Lonmin Mining Area and it is associated with known major faults. Sampling for the study has been collected from both Saffy East and Saffy West UG2 chromitite layers at Lonmin Platinum, to study any correlation or differences between the two chromitite layers on the east and west of Saffy Shaft. Channel sampling analysis, surface borehole analysis and underground mapping were all studied and interpreted for any differences that might have led to grade reduction or possible change in the ideal grade distribution. Underground mapping and observations have shown that areas affected by hydrothermal alteration dominate in linear geological structures such as minor faulting, intense jointing and thin veins. It has been observed that top contact of UG2 chromitite layer often exhibits shearing, which is associated with secondary mineralisation. In areas where the UG2 chromitite package is split by pyroxenite lenses, these pyroxenite lenses tends to show the effects of the hydrothermal alteration, such as discolouring and brittle behaviour. The channel sampling data from Saffy East altered chromitite areas contains approximately 2% less total PGE grade compared to less altered chromitite at Saffy West. The altered chromitite areas show less unintentional waste mining than less altered areas. Electron microprobe, scanning electron microscope analysis and petrography were conducted to analyse chemical variation in chromite grains, textural as well as mineralogical changes respectively. The petrographic analysis showed that plagioclase and orthopyroxene are the dominant minerals surrounding the chromite grains with clinopyroxenes in some Saffy East samples. Secondary minerals in Saffy East chromitite such as serpentine, biotite and talc are dominant especially within microstructures. Electron microprobe analysis of chromite showed an increase in aluminium and magnesium at Saffy East, where hydrothermal alteration is known to be prevalent; whereas Cr₂O₃ content is higher at Saffy West. The TiO₂ from both Saffy East and Saffy West shows similar values of approximately 1%, whereas the FeO is higher at Saffy East where the hydrothermal alteration is prevalent. The Cr# and Mg# of Saffy West and Saffy East chromite display slight variation with Saffy East chromite grains showing lower Cr# and higher Mg#; while the Saffy West chromite grains shows a slightly higher Cr# and lower Mg#. SEM studies have shown presence of PGM’s from both Saffy East and West chromite; the observed PGM’s are intercumulus to the matrix, they do not occur on the chromite grains.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science (Economic Geology) to the Faculty of Science, School of Geoscience, University of the Witwatersrand, Johannesburg, 2021